The TGF-β1/p53/PAI-1 Signaling Axis in Vascular Senescence: Role of Caveolin-1 - Rohan Samarakoon; Stephen P. Higgins; Craig E. Higgins; Paul J. Higgins (Biomolecules, 2019)
Stress-induced premature cellular senescence is a significant factor in the onset of age-dependent disease in the cardiovascular system. Plasminogen activator inhibitor-1 (PAI-1), a major TGF-β1/p53 target gene and negative regulator of the plasmin-based pericellular proteolytic cascade, is elevated in arterial plaques, vessel fibrosis, arteriosclerosis, and thrombosis, correlating with increased tissue TGF-β1 levels. Additionally, PAI-1 is necessary and sufficient for the induction of p53-dependent replicative senescence. The mechanism of PAI-1 transcription in senescent cells appears to be dependent on caveolin-1 signaling. Src kinases are upstream effectors of both FAK and caveolin-1 activation as FAKY577,Y861 and caveolin-1Y14 phosphorylation are not detected in TGF-β1-stimulated src family kinase (pp60c-src, Yes, Fyn) triple-deficient (SYF−/−/−) cells. However, restoration of pp60c-src expression in SYF-null cells rescued both caveolin-1Y14 phosphorylation and PAI-1 induction in response to TGF-β1. Furthermore, TGF-β1-initiated Src phosphorylation of caveolin-1Y14 is critical in Rho-ROCK-mediated suppression of the SMAD phosphatase PPM1A maintaining and, accordingly, SMAD2/3-dependent transcription of the PAI-1 gene. Importantly, TGF-β1 failed to induce PAI-1 expression in caveolin-1-null cells, correlating with reductions in both Rho-GTP loading and SMAD2/3 phosphorylation. These findings implicate caveolin-1 in expression controls on specific TGF-β1/p53 responsive growth arrest genes. Indeed, up-regulation of caveolin-1 appears to stall cells in G0/G1 via activation of the p53/p21 cell cycle arrest pathway and restoration of caveolin-1 in caveolin-1-deficient cells rescues TGF-β1 inducibility of the PAI-1 gene. Although the mechanism is unclear, caveolin-1 inhibits p53/MDM2 complex formation resulting in p53 stabilization, induction of p53-target cell cycle arrest genes (including PAI-1), and entrance into premature senescence while stimulating the ATM→p53→p21 pathway. Identification of molecular events underlying senescence-associated PAI-1 expression in response to TGF-β1/src kinase/p53 signaling may provide novel targets for the therapy of cardiovascular disease.